Fabrication and characterization of a Ni-TNTA bimetallic nanoelectrode to electrochemically remove nitrate from groundwater. (May 2019) - Liu, Fang; Liu, Kaiwang; Li, Miao; Hu, Senchang; Li, Jing; Lei, Xiaohui; Liu, Xiang
Abstract: A novel Ni-TiO2 nanotube array (Ni-TNTA) bimetallic nanometer electrode was developed. The electrode fabrication method was optimized, and the Ni-TNTA bimetallic nanoelectrode was used to efficiently remove nitrate from groundwater. The Ni-TNTA bimetallic nanoelectrode was prepared via an electrochemical method, chemical bath deposition method and calcining method. When the current density was 30 mA cm −2 after 90 min of electrolysis, the removal rate of nitrate was as high as 93.4%, whereas the removal rate of a TiO2 nanoelectrode made via the traditional method was only 56.0%. Under the same conditions, the newly developed Ni-TNTA bimetallic nanoelectrode increased the removal rate of nitrate by 66.8%. The results showed that the removal rate of nitrate was the highest when the Ni-TNTA bimetallic nanoelectrode was prepared with a 10 min chemical bath and calcination at 500 °C. The effect of the electrode on the removal rate of nitrate was investigated for different current densities, initial concentrations, temperature and pH. When the solution was alkaline, the removal efficiency of nitrate improved. When the current density and temperature increased, the removal rate of nitrate accordingly increased. However, as the initial concentration of the solution increased, the removal rate of nitrate decreased. An IrO2 electrode was used as the anode, the Ni-TNTA bimetallic nanoelectrode was used as the cathode, and 0.3 g L −1 NaCl was added into the solution. The removal rate of nitrate was 89.6% after 90 min of electrolysis and barely produced nitrite or ammonia. Highlights: A novel Ni-TNTA bimetallic nanoelectrode was fabricated. The novel nanoelectrode was used for electrochemical denitrification. The novel nanoelectrode has high reduction efficiency for nitrate. Very few by-products produced when added appropriate sodium chloride.